Digitalization of New Student Registration at the Salafiyah Baitul Kirom Islamic Boarding School - Nedi, Sanun; Jaya, Tobing Putra (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Salafiyah Baitul Kirom Islamic Boarding School, located in Mulyosari Village, Tanjungsari District, South Lampung Regency, Lampung Province, is an educational institution that contributes to shaping the younger generation through strong religious and moral values. However, the process of new student registration is still conducted conventionally through manual form completion and document submission via WhatsApp, resulting in inefficiency, time consumption, and a higher risk of administrative errors. This study aims to identify the problems in the existing new student registration process and to analyze the implementation of an online registration system as a solution to improve the admission process. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that the conventional registration system creates several obstacles, including slow administrative services, difficulties in data management, and limited access for prospective students living far from the boarding school. The implementation of an online registration system offers significant benefits in improving the efficiency, transparency, and accuracy of the registration process, while also reducing the administrative burden on the admission committee. In addition, the system facilitates better data management and provides easier access to information for prospective students. Therefore, the online registration system can serve as an effective solution to support the digital transformation of student admissions at Salafiyah Baitul Kirom Islamic Boarding School.